2004
DOI: 10.1016/j.jpdc.2004.05.005
|View full text |Cite
|
Sign up to set email alerts
|

STICS: SCSI-to-IP cache for storage area networks

Abstract: 7Data storage plays an essential role in today's fast-growing data-intensive network services. New standards and products emerge very rapidly for networked data storage. Given the mature Internet infrastructure, the overwhelming preference among the IT community 9 recently is using IP for storage networking because of economy and convenience. iSCSI is one of the most recent standards that allow SCSI protocols to be carried out over IP networks. However, there are many disparities between SCSI and IP in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…It enables clients to discover and access SCSI devices directly via the mature TCP/IP technology and existing Ethernet infrastructures. Previous work on iSCSI mainly concentrated on performance evaluation and potential improvements [15], [24], [31], [32]. By using our SPEK, we have evaluated the degraded performance of a popular iSCSI implementation and observed that the performance of iSCSI degrades dramatically in case of faults, but it can rapidly recover after such faults are removed or corrected.…”
Section: ) Iscsi and Stics Storage Area Networkmentioning
confidence: 99%
See 4 more Smart Citations
“…It enables clients to discover and access SCSI devices directly via the mature TCP/IP technology and existing Ethernet infrastructures. Previous work on iSCSI mainly concentrated on performance evaluation and potential improvements [15], [24], [31], [32]. By using our SPEK, we have evaluated the degraded performance of a popular iSCSI implementation and observed that the performance of iSCSI degrades dramatically in case of faults, but it can rapidly recover after such faults are removed or corrected.…”
Section: ) Iscsi and Stics Storage Area Networkmentioning
confidence: 99%
“…We have recently proposed a new storage architecture: SCSI-To-IP Cache Storage, or STICS for short [15]. The purpose of STICS is to bridge the disparities between SCSI and IP so that efficient SAN systems can be built over the Internet.…”
Section: ) Iscsi and Stics Storage Area Networkmentioning
confidence: 99%
See 3 more Smart Citations